Performance of Bragg grating assisted multi-band add-drop filters on the silicon-on-insulator platform. - Fernández-Hinestrosa, Alejandro; Luque-González, José Manuel; Cheben, Pavel; Schmid, Jens H.; Wang, Shurui; Wanguemert-Pérez, Juan Gonzalo; Molina-Fernández, Íñigo; Ortega-Moñux, Alejandro (My University, 2024)
In this work, we designed multi-band add-drop filters based on Bragg grating assisted Mach-Zehnder interferometers for the LAN wavelength division multiplexing standard. We experimentally assessed their behaviors on the silicon-on-insulator commercial platform. We experimentally report insertion losses of less than 1 dB and a mean interchannel crosstalk of -20 dB for a channel separation of 9 nm and a channel width of 3 nm
Keywords: Multiplexación; Comunicaciones ópticas; Fotónica integrada; Silicio sobre aislante; Redes de Bragg; Multiplexado por división en longitud de onda; Filtros add-drop